Automation of Microcontroller-Based Control System for Ph, Temperature, and Turbidity of Aquarium Water - Chorina Rosa Malik; Imam Sucahyo; Meta Yantidewi (IKIP Mataram, 2022)
This research is an experimental study to know the effectiveness of the control system for pH, temperature, and turbidity of aquarium water in ornamental fish cultivation. The method used is by assembling an automation tool for controlling the pH, temperature, and turbidity of the aquarium water based on a microcontroller, which is then compared with an aquarium without a control system. This tool is designed using the Arduino Uno as a system controller, the pH sensor E-201-C as a measuring tool for pH levels with a solenoid valve to drain pH up and pH down as a stabilizer for water pH levels, the DS18B20 sensor as a temperature measurement tool by utilizing a heater and DC fan as a water temperature stabilizer, and the turbidity sensor as a turbidity measurement tool with a clean water replacement system as a water turbidity stabilizer. Based on the experiments carried out, it was found that there were significant differences between aquariums using a control system automation tool compared to aquariums without a control system tool. This means that the system that is made is effective and proven to be able to maintain the environmental conditions of ornamental fish with measurement results of pH ranging from 7–7.5, the temperature of 24°–27°C, and water turbidity of 10 NTU.